Information ecology - Davenport, Thomas H. (Oxford University Press, 1997)
In Information Ecology, Thomas Davenport proposes a revolutionary new way to look at information management, one that takes into account the total information environment within an organization. Arguing that the information that comes from computer systems may be considerably less valuable to managers than information that flows in from a variety of other sources, the author describes an approach that encompasses the company's entire information environment, the management of which he calls information ecology. Only when organizations are able to combine and integrate these diverse sources of information, and to take them to a higher level where information becomes knowledge, will they realize the full power of their information ecology. Thus, the author puts people, not technology, at the center of the information world. Information and knowledge are human creations, he points out, and we will never excel at managing them until we give people a primary role. Citing examples drawn from his own extensive research and consulting including such major firms as A.T. & T